AN INNOVATIVE PRODUCT IN LINE WITH MODERN ENGINEERING MATERIALS AND DESIGN VALUES IS A TIME OF NEED - Yuldasheva Gulnora Buranovna; Khaidarova Gulnoza Bakhtiyorovna (American Journals Publishing, 2024)
In modern mechanical engineering, trends in the economy of energy and resources and ensuring optimal performance parameters of products for various functional purposes are obvious; a special place is occupied by the materials used, which must ensure the implementation of design solutions in compliance with technical requirements. documentation. Various operating conditions of technical equipment and increasing requirements for ergonomics, safety, repair and recycling require changes in traditional construction methods and new generation building materials. Modern structural materials must not only have operational characteristics parameters that correspond to the calculated values of the choice of design option, but also change these parameters during the operation of the product and ensure its adequate response to external conditions - temperature, temperature, speed, pressure. , composition of the environment, etc., the so-called concept of creating a product that meets the requirements at all stages of the life cycle of innovative products is one of the most pressing issues today. This article analyzes the methodological aspects of the selection of components of structural materials and the basis of polymer matrices used in the design of machines and technological equipment with increased performance indicators.
Keywords: Machine construction, trend, economy, energy, resource, material, technical, ergonomic, safety, construction, operation, adequate, reaction, temperature, speed, pressure.